Incorporating environmental sustainability issues into construction procurement at the district level in Ghana - Agyarko, Harold (2016)
A thesis submitted to the Department of Building Technology, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirement for the Degree of Master of Philosophy in Procurement Management.